1965
DOI: 10.1126/science.148.3676.1473
|View full text |Cite
|
Sign up to set email alerts
|

Paired Comparison Method for Measurement of Sugar Preference in Squirrel Monkeys

Abstract: The glucose preference of four squirrel monkeys was determined by presenting 5-, 10-, 20-, 30-, and 40-percent solutions according to the paired comparison method. Scaling of the data for the amounts of each solution consumed yielded a preference function which increased monotonically with the concentration of the solutions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

1971
1971
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 5 publications
1
10
0
Order By: Relevance
“…23 (lA) A second facotr is that of the measurement interval. A number of studies have shown that the measurement interval used may significantly affect the results obtained (e.g., Wagner, 1968;Wagner, Green, & Manley, 1965). The effects of measurement intervals are most clearly seen in the results of the second study of this paper.…”
Section: Resultssupporting
confidence: 62%
“…23 (lA) A second facotr is that of the measurement interval. A number of studies have shown that the measurement interval used may significantly affect the results obtained (e.g., Wagner, 1968;Wagner, Green, & Manley, 1965). The effects of measurement intervals are most clearly seen in the results of the second study of this paper.…”
Section: Resultssupporting
confidence: 62%
“…In order to simulate the daily observation and choice of fresh foodstuffs, we used the paired comparison method to measure perceived freshness. The paired comparison method has been used for measuring food preference [13] and visual preference for products [14], and is useful in the determination of preferences. This method allows us to measure freshness perception in comparisons of fresh foodstuffs in a manner that is close to a typical purchase situation.…”
Section: Introductionmentioning
confidence: 99%
“…The only other study reporting gustatory JND in non-human primates using a method similar to that used here yielded a value of 0.33 for glucose in squirrel monkeys although unphysiologically high concentrations were used and only rather coarse concentration steps were tested [4], Again, this value should be regarded as a conservative estimate of the ability to detect taste intensity differences.…”
Section: Discussionmentioning
confidence: 94%
“…This method has also been shown to be suit able for determining taste difference thresh olds, the so-called JND (just noticeable differ ence), for gustatory stimuli in monkeys [4],…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation